A versenyképesség és a jól-lét percepciói a Nyugat-Balkán államaiban a válság tükrében - Lőrinczné Bencze, Edit (Közép-Európai Közlemények, 2014)
Most of the Western Balkan countries have focused on economic integration with the Europe, on building up a functioning market economy and the capacity to cope with competitive pressure and market forces within the European Union. These efforts have led to a period of rapid catching up and SEE countries reported an average annual growth rate of 5.1% between 2000 and 2007. Despite the huge improvements the reforms came to a halt at an early stage in 2009 due to the economic crisis. The region’s economy has been declining since then mainly due to the fact that in the Western Balkan region the economic and political transformation process has been initiated rather late and all the structural changes have just been partially implemented. The current paper tries to track down the effects of the global economic crisis on the competitiveness of the countries in the Western Balkan region. The Western Balkan countries’ under%developed economies have been exposed to internal economic crises resulting from the economic transformation of their economies, macroeconomic instability, government mismanagement, and political reasons such as wars, sanctions, etc. The economic problems reflected not only in the Western-Balkan states’ macroeconomic indicators but also in the annual international competitiveness report (World Economic Forum). In order to improve the country’s competitiveness, market oriented economic reforms should be finished. The business environment needs to be strengthened, as well as R&D, innovation, FDI and private capital in order to further stimulate the economy.